Factors Associated with Uterine Atony in Mothers Experiencing Postpartum Hemorrhage at the Pasar Minggu District Health Center in 2023 - Suryani; Haris, Vera Suzana Dewi; Wahyunita, Vina Dwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Postpartum hemorrhage is the most common cause of maternal death. Primary postpartum hemorrhage is postpartum hemorrhage that occurs within the first 24 hours of birth. The purpose of this paper is to determine the factors associated with uterine atony in mothers who experience postpartum hemorrhage at the Pasar Minggu District Health Center in 2023. The research method used in this study is analytical with a cross-sectional approach to obtain factors related to independent and dependent variables, followed by analyzing the factors related to uterine atony in mothers who experience postpartum hemorrhage analytically. The results of the study showed that there was a relationship between age and uterine atony in mothers who experienced postpartum hemorrhage with an X2 hit value of 4.07, there was a relationship between parity and uterine atony in mothers who experienced postpartum hemorrhage with an X2 hit value of 6.64, there was no relationship between fetal weight and uterine atony in mothers who experienced postpartum hemorrhage with an X2 hit value of 0.524, there was a relationship between anemia status and uterine atony in mothers who experienced postpartum hemorrhage with an X2 hit value of 7.96, there was no relationship between the distance of delivery and uterine atony in mothers who experienced postpartum hemorrhage with an X2 hit value of 2.126. Conclusions and Suggestions age, parity, anemia status, are factors related to uterine atony in mothers who experienced postpartum hemorrhage, but fetal weight, and distance of delivery are not factors related to uterine atony in mothers who experienced postpartum hemorrhage. It is hoped that it will be able to detect complications early, encouraging mothers to have regular ANC check-ups at least 4 times during pregnancy.